2020
DOI: 10.1177/1747021819897882
|View full text |Cite
|
Sign up to set email alerts
|

Visual spatial attention and spatial working memory do not draw on shared capacity-limited core processes

Abstract: The extent to which similar capacity limits in visual attention and visual working memory indicate a common shared underlying mechanism is currently still debated. In the spatial domain, the multiple object tracking (MOT) task has been used to assess the relationship between spatial attention and spatial working memory though existing results have been inconclusive. In three dual task experiments, we examined the extent of interference between attention to spatial positions and memory for spatial positions. Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 68 publications
(109 reference statements)
0
7
0
1
Order By: Relevance
“…Third, the participants performed a change detection task that is indicative of VWM capacity rather than attention tasks (Qiu et al, 2018 ; Gan et al, 2020 ). Although VWM is closely related to several aspects of attention (Vogel et al, 2005 ; Astle and Scerif, 2011 ), visual attention and VWM share different key capacity-limited mechanisms (Howard et al, 2020 ). Thus, it is still unknown whether ARSG experience is related to an enhanced VWM capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the participants performed a change detection task that is indicative of VWM capacity rather than attention tasks (Qiu et al, 2018 ; Gan et al, 2020 ). Although VWM is closely related to several aspects of attention (Vogel et al, 2005 ; Astle and Scerif, 2011 ), visual attention and VWM share different key capacity-limited mechanisms (Howard et al, 2020 ). Thus, it is still unknown whether ARSG experience is related to an enhanced VWM capacity.…”
Section: Introductionmentioning
confidence: 99%
“…However, previous study has shown that spatial and non-spatial working memory are dissociable functions of the brain [ 40 ]. Howard et al’s study (2020) used MOT task, and found that for a purely spatial task, working memory and visual spatial attention appear to recruit separate capacity-limited resources [ 41 ]. Besides, several studies have also suggested that the resources of spatial working memory and visual spatial attention are independent of each other [ 42 , 43 , 44 , 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Performansi working memory (WM) terhadap informasi tidak relevan cukup ditandai dan diabaikan saja. Kapasitas WM selama memproses stimulus sangat ditentukan oleh upaya memfokuskan atensi dalam durasi waktu yang singkat pada stimulus tersebut (Fabius et al, 2017;Howard et al, 2020). Performansi kapasitas WM mengalami penurunan jika atensi makin melemah dan upaya meningkatkan kembali fokus atensi dikarenakan munculnya kembali informasi tidak relevan.…”
Section: Pembahasanunclassified